2020
DOI: 10.3390/e22091018
|View full text |Cite
|
Sign up to set email alerts
|

A Veritable Zoology of Successive Phase Transitions in the Asymmetric q-Voter Model on Multiplex Networks

Abstract: We analyze a nonlinear q-voter model with stochastic noise, interpreted in the social context as independence, on a duplex network. The size of the lobby q (i.e., the pressure group) is a crucial parameter that changes the behavior of the system. The q-voter model has been applied on multiplex networks, and it has been shown that the character of the phase transition depends on the number of levels in the multiplex network as well as on the value of q. The primary aim of this study is to examine phase transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(76 reference statements)
0
16
0
Order By: Relevance
“…However, it has been reported that the hysteresis appears in real social systems 1 5 , which means that this issue is important also from the social point of view. Because hysteresis cannot appear within the continuous phase transition, researchers working in the field of opinion dynamics try to determine conditions under which discontinuous phase transitions appear 6 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the hysteresis appears in real social systems 1 5 , which means that this issue is important also from the social point of view. Because hysteresis cannot appear within the continuous phase transition, researchers working in the field of opinion dynamics try to determine conditions under which discontinuous phase transitions appear 6 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In the first layer, we leveraged the q -voter model, which many scholars have studied extensively [ 33 , 40 , 41 , 42 , 43 ]. In our context, this assumes that each agent i has an opinion respecting the current restrictions, given by a binary variable: or .…”
Section: Methodsmentioning
confidence: 99%
“…Although it is a straightforward model, it has been applied to the characterization of various dynamical phenomena, such as the diffusion of innovation [ 30 ] or recurring fashion cycles [ 31 ]. It is also worth mentioning that, when considered in duplex and multiplex settings, the q -voter model provides a very rich behaviour with respect to the observed phase transitions [ 32 , 33 ]. Considering these observations, we eventually select the q -voter model due to its apparent simplicity and low number of tunable parameters that can lead to complex results.…”
Section: Introductionmentioning
confidence: 99%
“…Both the existence and the distinction between different types of phase transitions seems to be in the field of big interest of many researchers. This topic was not only reviewed from theoretical point of view in dynamical like models [1][2][3] but it appears in real social systems [4][5][6][7][8]. Through the need to establish certain universal laws, scientists are looking for factors which influence the appearance of discontinuous phase transitions.…”
Section: Introductionmentioning
confidence: 99%